The direction of books of jurisprudence differences and their components - Firdaus Firdaus (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2020)
There are many branches of Islamic jurisprudence and its sciences in several matters, including what are known as doctrinal differences, so what are the doctrinal differences? What is its definition of language? What is its meaning idiomatically as a note of this title? Finally, what is the scientific significance of the science of doctrinal differences? The importance of doctrinal differences is manifested in several matters. The most important of which are the following: highlighting the greatness of Islamic law, explaining its secrets, clarifying its intentions, clarifying its wisdom, and clarifying that the true Sharia came according to sound minds. So a distinction is made between similar one's appearance, by a judgment about each issue of the meaning he has made. Its jurisdiction required that provision, so he gave each item its proper understanding. Refute the nostalgia that has long been provoked by some prejudices who wage a violent campaign against Islamic jurisprudence and throw it in contradiction because of giving the symmetries different judgments, and settling them between the different. Controlling the jurisprudence and preserving it from misleading; it does not combine various issues and does not differentiate between similar matters.